Budaya Madura di Persimpangan Jalan (LPTNU Sumenep, 2022)
Globalization is a world reality where almost no place can escape the touch of globalization. Globalization makes the culture of an area can spread quickly depending on the mastery of technology. Regions that have mastery of high technology will quickly spread culture throughout the world. Meanwhile, areas that are lagging in technology must be prepared to experience cultural colonialism such as Madura. Madura is a province in East Java that has a very noble culture but is classified as backward in terms of mastery of technology. Therefore, globalization will threaten the noble culture of Madura if it is not immediately anticipated by all parties. The anticipatory attitudes that can be implemented are Maintaining Madura Cultural Levels, Learning from Madura Local Wisdom, and Revitalizing Local Culture and Local Communities as Actors.